Using deep learning algorithms to classify crop diseases - Murzabekova, Gulden; Glazyrina, Natalya; Nekessova, Anargul; Ismailova, Aisulu; Bazarova, Madina; Kashkimbayeva, Nurzhamal; Mukhametzhanova, Bigul; Aldashova, Madina (International Journal of Electrical and Computer Engineering (IJECE), 2023)
The use of deep learning algorithms for the classification of crop diseases is one of the promising areas in agricultural technology. This is due to the need for rapid and accurate detection of plant diseases, which allows timely measures to be taken to treat them and prevent their spread. One of them is to increase productivity and maintain land quality through the timely detection of diseases and pests in agriculture and their elimination. Traditional classification methods in machine learning and algorithms in deep learning were compared to note the high accuracy in detecting pests and crop diseases. The advantages and disadvantages of each model considered during training were taken into account, and the Inception V3 algorithm was incorporated into the application. They can monitor the condition of crops on a daily basis with the help of new technology-applications on gadgets. Aerial photographs used by research institutes and agricultural grain centers do not show the changes that occur in agricultural grains, that is, diseases and pests. Therefore, the method proposed in this paper determines the types of diseases and pests of cereals through a mobile application and suggests ways to deal with them.